Short term outcome of primary percutaneous coronary intervention (PCI) in patients with acute myocardial infarction - Zafar, Muhammad Kashif; Iqbal, Asim; Noeman, Ahmed; Akber, Nida Tasneem; Yousuf, Sohail; Faisal, Muhammad (Journal of Fatima Jinnah Medical University, 2022)
Background: Percutaneous Coronary intervention (PCI) is a routinely performed procedure in coronary care units. The aim of our study was to investigate the frequency of major adverse cardiac events (MACEs) after percutaneous coronary angiography in acute ST-elevation myocardial infarction (STEMI) patients in our institution. The objective of the study is to determine the frequency of MACEs after Percutaneous Coronary Intervention (PCI) in patients with acute myocardial infarction. Patients & Methods: This prospective observational study was carried out at Punjab Institute of Cardiology, Lahore from May 2017 to June 2017. A total 35 patients with STEMI who underwent Primary PCI were enrolled by consecutive sampling technique. An inclusion criterion was chest pain of 30 minutes to 12 hours duration with ECG showing ≥ 0.1mm ST-elevation in at least two contiguous leads. An exclusion criterion was thrombolysis within last 24 hours, malignancy, stroke and Left Main or equivalent disease on coronary Angiogram. Patients were followed after 2 weeks till 1 month for any MACES. (Including re-admission, need for repeat revascularization, stent thrombosis, recurrent acute MI, angina, stroke, and mortality). Frequency and percentages were calculated for MACEs by using SPSS 23.0. Results: Out of 35 cases, 34 (97.1%) were male and 1 (2.9%) were female. Mean age was 47.11±10.59 years, 14 (40%) patients had hypertension, 10 (28.6%) were diabetics and 12(34.3%) were current smokers while 4 (11.4%) were ex-smokers, 10 (28.6%) had family history of CAD, and 3 (8.6%) had hyperlipidemia. Successful revascularization with TIMI-III flow was attained in 34(97.1%) cases. 33minutes was mean door to balloon time. At one month follow-up, out of 35 patients, angina was reported only in 1 (2.9%) patient. There was no readmission, repeat revascularization, stent thrombosis, myocardial infarction, stroke and death reported in study subjects. Conclusion: Successful revascularization by Primary PCI was associated with very few early MACEs. For the treatment of coronary artery disease, PCI is an effective option. It has a few early MACEs and uses less contrast and has fewer distal complications than conventional angioplasty and invasive procedures.